Hyaluronic acid-based supramolecular medicine with polyamines sequestration capability for cooperative anti-psoriasis. (15th November 2022) - Ding, Yuan-Fu; Wei, Jianwen; Quan, Xingping; Gu, Wenting; Xi, Long; Zheng, Ying; Zhao, Yonghua; Luo, Jingwei; Li, Shengke; Mok, Greta S.P.; Wang, Ruibing
Abstract: Psoriasis seriously harms physical and mental health of patients. Hyaluronic acid (HA)-based topical formulation can increase drug concentration in psoriatic skin via CD44-assisted targeting. Herein, we developed a supramolecular medicine composed of curcumin-loaded HA-cucurbit[7]uril (HA-CB[7]@Cur), which could efficiently sequester polyamines (PAs) via host-guest interactions of CB[7] and PAs to suppress RNA-PAs immunocomplex formation. Meanwhile, anti-psoriasis drug Cur could be released from HA-CB[7]@Cur by PAs. With phenotypical disease evaluation, psoriasis area measurements and severity index scoring, and histological characterizations, we demonstrate topical administration of Carbopol gel formulation of HA-CB[7]@Cur on psoriasis-like skin in mice exhibited an enhanced anti-psoriasis activity, in comparison with gel of free Cur or HA-CB[7]. Cytokine expression analysis in psoriatic skin also supported the observed therapeutic outcomes. We provide a novel and effective supramolecular strategy to realize cooperative anti-psoriasis via controlled release of curcumin and PAs sequestration, which can be potentially expanded to treat other PA-involved skin inflammatory diseases. Graphical abstract: Unlabelled Image